miR-155 Modifies Inflammation, Endothelial Activation and Blood-Brain Barrier Dysfunction in Cerebral Malaria - Kevin R. Barker; Ziyue Lu; Hani Kim; Ying Zheng; Junmei Chen; Andrea L. Conroy; Michael Hawkes; Henry S. Cheng; Makon-Sébastien Njock; Jason E. Fish; John M. Harlan; Jose A. López; et al. (BMC, 2017)
Abstract miR-155 has been shown to participate in host response to infection and neuroinflammation via negative regulation of blood-brain barrier (BBB) integrity and T cell function. We hypothesized that miR-155 may contribute to the pathogenesis of cerebral malaria (CM). To test this hypothesis, we used a genetic approach to modulate miR-155 expression in an experimental model of cerebral malaria (ECM). In addition, an engineered endothelialized microvessel system and serum samples from Ugandan children with CM were used to examine anti-miR-155 as a potential adjunctive therapeutic for severe malaria. Despite higher parasitemia, survival was significantly improved in miR-155−/− mice versus wild-type littermate mice in ECM. Improved survival was associated with preservation of BBB integrity and reduced endothelial activation, despite increased levels of proinflammatory cytokines. Pretreatment with antagomir-155 reduced vascular leak induced by human CM sera in an ex vivo endothelial microvessel model. These data provide evidence supporting a mechanistic role for miR-155 in host response to malaria via regulation of endothelial activation, microvascular leak and BBB dysfunction in CM.